Pemanfaatan Komik Digital Sebagai Media Pembelajaran Di Sekolah Dasar - I Nyoman Urip; Renol Renol; Heri Kusuma Tarupay (Satya Sastraharing : Jurnal Manajemen, 2023)
The learning process requires media to make it easier for student to understand the learning materials. This article discusses the use of Digital Comics or illustrated stories as learning media for elementary school student. Digital comics offer images and dialogues that can serve as a means of delivering learning materials to elementary school student. Picture can capture students attention and focus on learning, while dialogues provide a space to insert learning materials. The ai of this research is to examine the use of Digital Comics as an alternative learning media for elementary school students. The method used is literature review (library research). Digital Comics as a learning media are considered capable of supporting enjoyable learning and increasing vocabulary knowledge, preventing students from getting bored quickly.